2015
DOI: 10.1002/pmic.201400510
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and network analysis of proteins regulated by REX1 in human embryonic stem cells

Abstract: Recent studies have suggested that REX1 (reduced expression 1) plays an important role in pluripotency, proliferation, and differentiation. However, the molecular mechanisms involved in REX1-dependent regulation of diverse cellular processes remain unclear. To elucidate the regulatory functions of REX1 in human embryonic stem cells (hESCs), comparative proteomic analysis was performed on REX1 RNAi specifically silenced hESCs. Analysis of the proteome via nano-LC-MS/MS identified 140 differentially expressed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Details of the 2D and 3D culture methods used for HepaRG cells are provided in the http://onlinelibrary.wiley.com/doi/10.1002/hep.29324/suppinfo. The hESC cell line H9 (WiCell Research Institute, Madison, WI) and human iPSCs generated from fibroblasts as described were maintained on Matrigel (BD Biosciences, San Jose, CA)–coated dishes in mTeSR 1 medium (STEMCELL Technologies, Temecula, CA) …”
Section: Methodsmentioning
confidence: 99%
“…Details of the 2D and 3D culture methods used for HepaRG cells are provided in the http://onlinelibrary.wiley.com/doi/10.1002/hep.29324/suppinfo. The hESC cell line H9 (WiCell Research Institute, Madison, WI) and human iPSCs generated from fibroblasts as described were maintained on Matrigel (BD Biosciences, San Jose, CA)–coated dishes in mTeSR 1 medium (STEMCELL Technologies, Temecula, CA) …”
Section: Methodsmentioning
confidence: 99%
“…The ratios describing the condition virulent/milder species of two comparative models ( R. slovaca / R. raoultii and R. conorii / R. massiliae ) were then log 2 transformed. Orthologous proteins with stringently defined fold change (FC ≥ 2) were considered to represent up-regulation (log 2 ratio ≥ 1) or down-regulation (log 2 ratio ≤ −1), whereas orthologous proteins with a FC < 2 were considered as equally regulated (Son et al, 2015). Proteins with FC = 2 included a minimal and a well-represented abundance value of 0.5 fmol.…”
Section: Methodsmentioning
confidence: 99%
“…REX1 is expressed in several organs, including the brain, and plays an important role in differentiation, proliferation, and pluripotency. Recent proteomic and network analysis of proteins regulated by REX1 in human embryonic stem cells revealed that it affects several intracellular processes, including translation, regulation of mitochondrial processes, and specific differentiation [74], which might be affected in the patients with RLIM variants.…”
Section: Discussionmentioning
confidence: 99%